Pocket CIO – The Guide to Successful IT Asset Management : Get to grips with the fundamentals of IT Asset Management, Software Asset Management, and Software License Compliance Audits with this handy guide /: Get to grips with the fundamentals of IT Asset Management, Software Asset Management, and Software License Compliance Audits with this handy guide. (2018) - McLachlan, Phara
No abstract available